2023
DOI: 10.1111/1541-4337.13199
|View full text |Cite
|
Sign up to set email alerts
|

Termites as human foods—A comprehensive review

Abstract: Global food production is anticipated to rise along with the growth of the global population. As a result, creative solutions must be devised to ensure that everyone has access to nutritious, affordable, and safe food. Consequently, including insects in diets has the potential to improve global food and nutrition security. This paper aims to share recent findings by covering edible termites as the main aspect, from their consumption record until consumer acceptance. A total of 53 termite species are reported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 225 publications
0
2
0
Order By: Relevance
“…Low to high intensity of blue color represent least to high number of species consumption, respectively, in each country. Estrada et al, 2021;Siddiqui et al, 2023a). Hence, it is necessary to search for alternative natural resources to combat this situation.…”
Section: Records Of Consumption and Consumer Acceptance Of Edible Bla...mentioning
confidence: 99%
See 1 more Smart Citation
“…Low to high intensity of blue color represent least to high number of species consumption, respectively, in each country. Estrada et al, 2021;Siddiqui et al, 2023a). Hence, it is necessary to search for alternative natural resources to combat this situation.…”
Section: Records Of Consumption and Consumer Acceptance Of Edible Bla...mentioning
confidence: 99%
“…Earlier, European Food Safety Authority (EFSA) Scientific Committee has recorded 12 insect species as potential a food source; house cricket (Acheta domesticus), American grasshopper (Schistocerca americana), banded cricket (Gryllodes sigillatus), black soldier fly (Hermetia illucens), African migratory locust (Locusta migratoria migratorioides), housefly (Musca domestica), honeycomb moth (Galleria mellonella), silkworm (Bombyx mori), lesser wax moth (Achroia grisella), superworm (Zophobas atratus), lesser mealworm (Alphitobius diaperinus), and mealworm (Tenebrio molitor) (EFSA, 2015). According to Siddiqui et al (2023a), there are more than 2000 species of insects that have been identified as edible, but only 80% of these are confirmed suitable for human consumption, and 4% have been recognised to have medicinal value (van Itterbeeck and Pelozuelo, 2022). In developing nations, notably in regions namely Sub-Saharan Africa and South Asia are incorporating edible insects as a dietary food source (Tao and Li, 2018;Hlongwane et al, 2020).…”
Section: Introductionmentioning
confidence: 99%